TIPE PEMBUKTIAN MAHASISWA CALON GURU MATEMATIKA - Mu'jizatin Fadiana; Yulaikah Yulaikah; Lajianto Lajianto (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
The ability to prove formal mathematics is an important ability that must be mastered by undergraduate prospective mathematics teachers. However, students who are prospective mathematics teachers have difficulty in constructing proof in mathematics courses. Therefore, this study aims to explore the tendency of mathematical proof methods for prospective mathematics teachers in second year lectures. The method used in this research is quantitative descriptive research. Participants in this study were 30 prospective mathematics teachers at a tertiary institution in Tuban, East Java. The research instrument is a simple task of compiling mathematical evidence. The results of the study were analyzed using the classification of types of proof by Miyazaki, namely classifying the types of deductive and inductive reasoning. The results showed that prospective mathematics teachers had a greater tendency to use deductive reasoning than using inductive reasoning. Type A proof is the most common type of proof. In addition, around 70% of prospective teachers still experience difficulties in compiling evidentiary tasks.